2021
DOI: 10.3389/fmed.2021.737079
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Articular Manifestations and Comorbidities in Psoriatic Disease: A Journey Into the Immunologic Crosstalk

Abstract: Psoriatic arthritis (PsA) is a chronic inflammatory disease primarily affecting peripheral and axial joints, with the possible presence of extra-articular manifestations (EAMs), such as psoriasis, uveitis, and inflammatory bowel disease. Recently, the concept of psoriatic disease (PsD) has been proposed to define a systemic condition encompassing, in addition to joints and EAMs, some comorbidities (e.g., metabolic syndrome, type II diabetes, hypertension) that can affect the disease outcome and the achievement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 153 publications
0
19
0
Order By: Relevance
“…6 Type 2 diabetes mellitus, cardiovascular diseases, hyperlipidemia, hypertension, and fibromyalgia have been identified as key co-morbid factors that guide the initiation and progression of PsA. 7 A few recent studies, [8][9][10] includ-ing our own earlier work, 11 have suggested a potential link between PD and PsA because both conditions share a number of remarkable traits, including bone resorption and altered bone remodeling, cell infiltration, a heightened immune response to microorganisms living on the epidermal surface of the skin or in periodontal tissues, and shared risk factors. 10,12 In fact, PD can be seen as a pertinent concern in psoriatic arthritis patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 Type 2 diabetes mellitus, cardiovascular diseases, hyperlipidemia, hypertension, and fibromyalgia have been identified as key co-morbid factors that guide the initiation and progression of PsA. 7 A few recent studies, [8][9][10] includ-ing our own earlier work, 11 have suggested a potential link between PD and PsA because both conditions share a number of remarkable traits, including bone resorption and altered bone remodeling, cell infiltration, a heightened immune response to microorganisms living on the epidermal surface of the skin or in periodontal tissues, and shared risk factors. 10,12 In fact, PD can be seen as a pertinent concern in psoriatic arthritis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriatic disease is accompanied by extracutaneous and extra-articular manifestations, as well as by a wide range of comorbidities. Compared with controls, patients with psoriatic disease have a higher incidence rate of other autoimmune diseases, cardiovascular disease, obesity/overweight, depression, anxiety, smoking, cancer, diabetes, alcohol abuse, osteoporosis, uveitis, and fatty liver disease [ 45 ]. One of the common connectors between the disease and its comorbidities is inflammation.…”
Section: Nf-κb Genetic Variants and Cardiometabolic Comorbiditymentioning
confidence: 99%
“…IL-17, one of PsA signature cytokines, promotes bone resorption via RANK ligand upregulation. Indeed, Th17 cells have been found to be highly increased in blood and tissues of patients with OP [ 45 ].…”
Section: Nf-κb Genetic Variants and Cardiometabolic Comorbiditymentioning
confidence: 99%
“…Moreover, extra-articular manifestations, including gastrointestinal, anterior ocular, cardiovascular, and non-psoriatic cutaneous involvement, might be found in up to 35% of patients with PsA and in up to 50% of BS patients, further complicating the differential diagnosis [2,[12][13][14]. Notably, common immunopathogenic pathways, including among others key cytokines such as tumor necrosis factor (TNF) alpha, interleukin (IL-17), IL12 and IL23, sustain articular and extra-articular manifestations in both diseases [1,6,[15][16][17]. The relationship between BS and PsA is also supported by the recent evidence that BS patients present a significantly increased risk of psoriasis, and still greater risk of PsA, being twice more vulnerable to PsA as compared to non-BS subjects [13].…”
Section: Introductionmentioning
confidence: 99%